A central region of Ku80 mediates interaction with Ku70 in vivo. - Cary, R B (1998)
Ku, the DNA binding component of DNA-dependent protein kinase (DNA-PK), is a heterodimer composed of 70 and 86 kDa subunits, known as Ku70 and Ku80 respectively . Defects in DNA-PK subunits have been shown to result in a reduced capacity to repair DNA double-strand breaks. Assembly of the Ku heterodimer is required to obtain DNA end binding activity and association of the DNA-PK catalytic subunit. The regions of the Ku subunits responsible for heterodimerization have not been clearly defined in vivo . A previous study has suggested that the C-terminus of Ku80 is required for interaction with Ku70. Here we examine Ku subunit interaction using N- and C-terminal Ku80 deletions in a GAL4-based two-hybrid system and an independent mammalian in vivo system. Our two-hybrid study suggests that the central region of Ku80, not its C-terminus, is capable of mediating interaction with Ku70. To determine if this region mediates interaction with Ku70 in mammalian cells we transfected xrs-6 cells, which lack endogenous Ku80, with epitope-tagged Ku80 deletions carrying a nuclear localization signal. Immunoprecipitation from transfected cell extracts revealed that the central domain identified by the GAL4 two-hybrid studies stabilizes and co-immunoprecipitates with endogenous xrs-6 Ku70. The central interaction domain maps to the internally deleted regions of Ku80 in the mutant cell lines XR-V9B and XR-V15B. These findings indicate that the internally deleted Ku80 mutations carried in these cell lines are incapable of heterodimerization with Ku70.